2008
DOI: 10.1186/1471-2458-8-15
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of delay in the diagnosis and treatment of tuberculosis

Abstract: Background: Early diagnosis and immediate initiation of treatment are essential for an effective tuberculosis (TB) control program. Delay in diagnosis is significant to both disease prognosis at the individual level and transmission within the community. Most transmissions occur between the onset of cough and initiation of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

68
731
12
40

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 801 publications
(883 citation statements)
references
References 16 publications
68
731
12
40
Order By: Relevance
“…Patients have to visit health services on their own for diagnosis [passive case finding (PCF)], and only after TB diagnosis does the programme takes up active responsibility to care for them [9]. The process to reach the health facilities could be time-consuming, cumbersome and costly [1012]. As TB services are integrated with the general health system, the geographical, financial and social access barriers to TB care are similar to the barriers of accessing the general health system [4,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients have to visit health services on their own for diagnosis [passive case finding (PCF)], and only after TB diagnosis does the programme takes up active responsibility to care for them [9]. The process to reach the health facilities could be time-consuming, cumbersome and costly [1012]. As TB services are integrated with the general health system, the geographical, financial and social access barriers to TB care are similar to the barriers of accessing the general health system [4,13].…”
Section: Introductionmentioning
confidence: 99%
“…As TB services are integrated with the general health system, the geographical, financial and social access barriers to TB care are similar to the barriers of accessing the general health system [4,13]. Patients get trapped in a vicious circle of repeated visits to the same health care provider (HCP) or visits to multiple HCPs including private and traditional HCPs [8,10,11,14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…In this framework, the transmission rate, frequency of health-system contact and probability of successful diagnosis can all change S61 over time 19 . As an illustration, if patients remain infectious for an average of 10 months before seeking care and then begin to contact the health system once a month 28,29 , a 50% chance of successful diagnosis per visit would still result in a mean duration of infectiousness of 1 year -but increasing the probability of diagnosis from 0.5 to 0.75 would only reduce that duration to 11.3 months. Worse still, if most transmissions occur in the first 10 months, then even a perfect diagnostic test at the health facility could not avert those events.…”
mentioning
confidence: 99%
“…Previous studies have shown that a delay in diagnosis is closely related to poor access to health care 8,9 . Despite TB control programs' recommendation that diagnosis should be made at the primary health care level, most patients are still diagnosed in hospitals.…”
Section: Introductionmentioning
confidence: 99%